2005
DOI: 10.1521/aeap.17.3.119.62903
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence, Correlates, and Costs of Depression in People Living With HIV/AIDS in Ontario: Implications for Service Directions

Abstract: As new technologies extend the lives of people living with HIV/AIDS (PHA), the need increases for services that optimize their quality-of-life cost effectively. This study of PHAs (n = 297) in Ontario, Canada, examined the prevalence of depression, and its association with quality-of-life, coping strategies, social support, and use of health and social services. Results showed that depression was widespread (54.2%) and largely unrelated to demographic characteristics, but associated with diminished health stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
1
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 15 publications
1
43
1
4
Order By: Relevance
“…These findings were consistent with several studies in western countries which demonstrated the efficacy of CBT for HIV-infected patients with depression in diverse populations [15,33,[39][40][41]. In addition, our study demonstrated that, immediately and 3-month post-treatment, the mean TDI score among patients in the CBT group decreased substantially from the baseline.…”
Section: Disscussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These findings were consistent with several studies in western countries which demonstrated the efficacy of CBT for HIV-infected patients with depression in diverse populations [15,33,[39][40][41]. In addition, our study demonstrated that, immediately and 3-month post-treatment, the mean TDI score among patients in the CBT group decreased substantially from the baseline.…”
Section: Disscussionsupporting
confidence: 92%
“…Several studies have shown that depression was significantly associated with poor adherence to highly active antiretroviral therapy (HAART) [3,[10][11][12][13][14]. This resulted in drug resistance mutation and treatment failure [8] which increased patients' health care costs [3,15] and affected their quality of life as well as health outcomes [16,17]. Similarly, depression has been related to faster increase in plasma HIV viral load, more rapid decline in CD4+T lymphocyte cells count [18] and progression to AIDS, and increased mortality [19].…”
Section: Introductionmentioning
confidence: 99%
“…negative feelings among MSM towards formal health service structures whose staff may be unsympathetic. 35 Some participants in our study who interrupted their own HIV care emphasized their anger and disappointment in the prejudice and disrespect they perceived from healthcare workers. Previous studies also suggested that HIV/AIDS stigmatizing and discriminatory attitudes from healthcare providers hindered the utilization of HIV prevention, care and treatment.…”
Section: Discussionmentioning
confidence: 81%
“…individuals have been estimated as high as 43 % (Chandra et al 1998;Perretta et al 1996). Likewise, depressive symptoms and disorders commonly co-occur with HIV/AIDS, with some studies finding over a 50 % base rate of clinical depression among adults with HIV/AIDS (Williams et al 2005). Although the underlying directionality between anxiety and depressive symptoms and disorders and HIV/AIDS is presently unclear, research has nonetheless found that these negative emotional states tend to contribute to non-adherence to HIV medications (Antoni 2003;DiMatteo et al 2000;Schönnesson et al 2006;van Servellen et al 2002), lesser quality of life (Sewell et al 2000), greater health-care utilization (Joyce et al 2005;O'Cleirigh et al 2009), and greater risky sexual behaviors (Hart et al 2008;Hatzenbuehler et al 2011).…”
Section: Introductionmentioning
confidence: 99%